Heritage languages and language as heritage: the language of heritage in Canada and beyond. Issue 7 (3rd July 2022) - Eaton, Jonathan; Turin, Mark
ABSTRACT: This article draws on recent discourses surrounding intangible cultural heritage (ICH) and its relationship to language preservation, practice, and revitalisation to propose that language be considered a form and practice of heritage in and of itself, not merely a vehicle for the conveyance of ICH. As such, language can serve as a bridge between the often-parallel tracks of tangible and intangible heritage, helping arrive at an understanding of heritage that is broader, more nuanced, and more inclusive. Until now, most scholars have resisted fully characterising language as heritage, viewing 'heritagisation' as a threat to the vitality of language rather than embracing language as a boon to the aliveness of heritage. In support of our argument, we draw on examples from Latin America, Asia, and in particular Canada to highlight specific historical and political discourses that determine whose language counts as heritage and whose heritage counts more generally. While certain communities may derive some benefit from an acknowledgement of their language as a form of heritage in service of a language reclamation agenda, the field of heritage will benefit greatly from inviting the vitality of language to enrich its many facets – discourse, practice, materiality, and the interplay among these three.